Translational Biophotonics: Diagnostics and Therapeutics 2021
DOI: 10.1117/12.2615012
|View full text |Cite
|
Sign up to set email alerts
|

Brightness controller optimization for the digital diaphanoscopy system

Abstract: In this work, the LED applicator brightness control unit of the digital diaphanoscope was upgraded, which allows adjusting of the radiation power value in a wide range for patient's study, considering anatomical and gender features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In addition, a preliminary numerical simulation of the radiation propagation through the tissues of the maxillary sinus was carried out. The results obtained made it possible to justify the selected wavelengths as optimal for the study [30,31]. Preliminary studies have shown that the recorded diaphanograms are strongly influenced by the value of the optical power of the LED applicator, which is due to the difference in the anatomical structure of the tissues of the maxillary sinuses in male and female (e.g., the thickness of the hypodermis, the size of the maxillary sinuses, etc.).…”
Section: Experimental System and Methodologymentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, a preliminary numerical simulation of the radiation propagation through the tissues of the maxillary sinus was carried out. The results obtained made it possible to justify the selected wavelengths as optimal for the study [30,31]. Preliminary studies have shown that the recorded diaphanograms are strongly influenced by the value of the optical power of the LED applicator, which is due to the difference in the anatomical structure of the tissues of the maxillary sinuses in male and female (e.g., the thickness of the hypodermis, the size of the maxillary sinuses, etc.).…”
Section: Experimental System and Methodologymentioning
confidence: 98%
“…In order to assess the influence of the optical power values, numerical simulation was carried out with the establishment of different values of the optical power for male and female. The choice of optical power values was carried out in accordance with the capabilities of the previously developed LED brightness controller of the digital diaphanoscope [32]. As a result, it was found that for female patients, the optimal optical power is 35/40 mW (650 nm) and 25/65 mW (850 nm), whereas for male patients, these values amount 55/60 mW (650 nm) and 80/85 mW (850 nm), respectively.…”
Section: Experimental System and Methodologymentioning
confidence: 99%